Dua Flavonoid Tergeranilasi dari Daun Sukun (Artocarpus altilis) - Yana Maolana Syah; Sjamsul Arifin Achmad; Eri Bakhtiar; Euis Holisotan Hakim; Lia Dewi Juliawaty; Jalifah Latip (Institut Teknologi Bandung, 2006)
Two geranylated flavonoid derivatives, namely 2-geranyl-2,4,3,4-tetrahydroxydihydrochalcone (1) and 8-geranyl-4,5,7-trihydroxy-flavanone (2), had been isolated from methanol extract of the leaves of sukun (Artocarpus altilis). The structures of the two compounds were determined based on UV, IR, 1H NMR and 13C NMR spectra, and by comparing with the previously reported data. The presence of these two compounds in A. altilis indicated that the leaves of Artocarpus plants tend to produce more simple flavonoids. Â